Rehabilitasi Penyalahguna Narkotika Dengan Double Track System Dalam Pemidanaan Di Indonesia - Sitta Saraya; Yusrina Handayani (ADIL Indonesia Journal, 2023)
Rehabilitation for Narcotics Abusers with a Double Track System in Criminal Cases in Indonesia (Case Study of Supreme Court Decision Number 2281 K/Pid.Sus/2016). Narcotics abusers by law must be given a sentence in the form of imprisonment as an effort to provide a deterrent effect for the actions they commit. Abusers should receive rehabilitation in the form of medical and social as an effort to provide awareness to the abusers themselves so that the desire to abuse narcotics disappears after receiving the rehabilitation process even though the imposition of criminal sanctions is still important. The research conducted in this article uses a normative juridical method by applying the legal principles to Article 127 of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics related to the provision of punishment for narcotics abusers accompanied by a stipulation of the obligation to obtain rehabilitation which is deducted from the length of imprisonment imposed on drug abusers narcotics, especially class I, such as methamphetamine or better known as methamphetamine, which is widely abused because it circulates in large quantities in society, as happened to the defendant who was tried for abusing narcotics in the Supreme Court decision Number 2281 K/Pid.Sus/2016. In addition to Law Number 35 of 2009 concerning Narcotics, provisions stipulated in the Attorney General's Regulations and the Supreme Court Circular regarding the placement of narcotics abusers in rehabilitation institutions will also be discussed. In general, this is what is known as the double track system in the criminal justice system in Indonesia. it is concluded that the double track system must be in sentencing for narcotics abusers, although it has not touched on the effectiveness of the length of rehabilitation which will greatly affect the results of rehabilitation for narcotics abusers which consists of medical and social rehabilitation.  Abstrak Rehabilitasi Bagi Penyalahguna Narkotika Dengan Double Track System Dalam Pemidanaan Di Indonesia (Studi Kasus Putusan Mahkamah Agung Nomor 2281 K/Pid.Sus/2016). Penyalahguna narkotika secara undang-undang harus diberikan pidana berupa penjara sebagai upaya untuk memberikan efek jera atas perbuatan yang dilakukannya. Penyalahguna seharusnya mendapatkan rehabilitasi berupa medis dan sosial sebagai upaya untuk memberikan kesadaran terhadap diri penyalahguna tersebut sehingga keinginan untuk nmenyalahgunakan narkotika tersebut hilang setelah mendapatkan proses rehabilitas meskipun pemberian sanksi pidana tetaplah penting adanya. Penelitian yang dilakukan dalam artikel ini dengan metode yuridis normatif dengan menerapkan asas hukum pada Pasal 127 Undang-Undang Republik Indonesia Nomor 35 Tahun 2009 tentang Narkotika terkait pemberian pidana bagi penyalahguna narkotika disertai dengan penetapan kewajiban mendapatkan rehabilitasi yang dikurangkan dari lama pidana penjara yang dijatuhkan terhadap penyalahguna narkotika terutama golongan I seperti metamfetamina atau yang lebih dikenal dengan sabu-sabu yang banyak disalahgunakan karena beredar dalam jumlah yang banyak di masyarakat sebagaimana yang terjadi pada terdakwa yang diadili karena menyalahgunakan narkotika dalam putusan Mahkamah Agung Nomor 2281 K/Pid.Sus/2016. Selain Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika maka akan dibahas pula ketentuan yang diatur dalam Peraturan Jaksa Agung, dan Surat Edaran Mahkamah Agung dalam hubungannya dengan penempatan penyalahguna narkotika di lembaga rehabilitasi. Secara umum inilah yang dikenal dengan double track system dalam system pemidanaan di Indonesia. Kesimpulan penelitian ini adalah harus ada penerapan double track system dalam pemidanaan bagi penyalahguna narkotika meskipun belum menyentuh kepada keefektifitasan lamanya rehabilitasi yang akan sangat mempengaruhi hasil dari rehabilitasi bagi penyalahguna narkotika yang terdiri dari rehabilitasi medis dan sosial.